The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1128/jcm.01488-07
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors in Urinary Escherichia coli Strains: Phylogenetic Background and Quinolone and Fluoroquinolone Resistance

Abstract: Quinolone-and fluoroquinolone-resistant Escherichia coli strains harbor fewer virulence factors than susceptible strains. The reasons underlying this correlation are incompletely understood. We investigated the phylogenetic background, the presence of the papC, hlyA, and cnf1 (pathogenicity island II J96 -associated), fimA, iss, and iutA genes, and the presence of type 1 fimbriae, P fimbriae, and hemolysin in 243 urinary E. coli isolates resistant only to quinolones (8%), resistant to both quinolones and fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
61
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 45 publications
32
61
4
1
Order By: Relevance
“…In this study, only 10 % of the UPEC isolates examined had haemolytic activity, and only 10 % of these isolates carried the hlyA gene. Recently, the hlyA gene was found to be overwhelmingly associated with the B2 group of UPEC: 34 % of B2 group strains carried the hlyA gene while only 4 % of group A, 5 % of group B1 and 2 % of group D strains possessed this gene (Piatti et al, 2008). In our study, 30 % of B2 group strains (23/77) were hlyA positive.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, only 10 % of the UPEC isolates examined had haemolytic activity, and only 10 % of these isolates carried the hlyA gene. Recently, the hlyA gene was found to be overwhelmingly associated with the B2 group of UPEC: 34 % of B2 group strains carried the hlyA gene while only 4 % of group A, 5 % of group B1 and 2 % of group D strains possessed this gene (Piatti et al, 2008). In our study, 30 % of B2 group strains (23/77) were hlyA positive.…”
Section: Discussionsupporting
confidence: 52%
“…Although there are several mechanisms for the development of resistance, mutation in the gyrA gene is the most common. 16 The high occurrence of ciprofloxacin resistance (75.9%) in our isolates is in accordance with some other reports from Asia, 15,17 but it is in contrast to a report from Vietnam. 18 As expected, the incidence of resistance to nalidixic acid, which is a simple quinolone, was higher (93.1%) and in agreement with some earlier reports.…”
Section: Discussionsupporting
confidence: 92%
“…Quinoloneresistant isolates were significantly associated with low incidence of papAH, papC, sfa/focDE, iutA, and kpsMT II, which supports a previous finding [46]. Soto et al [47] reported that uropathogenic E. coli strains exposed to sub-inhibitory concentrations of quinolones showed partial or total loss of PAIs (pathogenicity islands) containing virulence factor genes.…”
Section: Discussionsupporting
confidence: 75%